Demonstration and scaling of integrated management of parasitic weeds on faba bean in Northern Ethiopia and Morocco - Kassaw, Admasie; Abtie, Abate; Assaye, Gebremariam; Abathun, Tamir; Esmael, Jemal; Mihiretie, Aderajew; Mengi, Yechale; Alem, Cherinet; Bencheqroun, Sanae Krimi; Boughlala, Mohamed; Elwazziki, Hanane; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2023)
Cool-season food legumes (faba bean, field pea, chickpea and lentil) are important crops for food, income generation, animal feed and improving soil fertility through nitrogen fixation in Ethiopia and Morocco. The productivity and acreage of these crops are decreasing due to diseases, insect pests and parasitic weeds. Parasitic weeds (Orobanche and Phelipanche spp.) play more damaging roles than other biophysical constraints in North Africa and Ethiopia. No single control measure is effective in minimizing the damaging of parasitic weeds in food legumes. Therefore, demonstration and scaling of integrating control options can play roles in minimizing yield gaps caused by parasitic weeds.